Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Functions f , g : R → R are defined, respectively, by f (x) = x2 + 3x + 1, g (x) = 2x – 3, find f o g

 Functions f , g : R → R are defined, respectively, by f (x) = x2 + 3x + 1, g (x) = 2x – 3,
find  f o g  

Grade:12

1 Answers

Harshit Singh
askIITians Faculty 5872 Points
5 months ago
Dear Student

Given that,
f(x)=x^2+3x+1
g(x)=2x–3

fog = f(g(x))

= f(2x - 3)
= (2x-3)^2+3(2x-3) + 1
= 4x^2+9–12x + 6x–9 + 1
= 4x^2–6x+1

Thanks


Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free